2014
DOI: 10.1097/bsd.0b013e3182a180fc
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Outcome and the Surgical Strategy of Percutaneous Endoscopic Discectomy for Recurrent Disk Herniation

Abstract: The relevant utilization of updated surgical techniques may be helpful in overcoming the difficulty of revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…Fusion surgery was required only in 1 patient. The dural injury risk in microendoscopic discectomy has been reported to be higher than in microsurgery [20,22]. Ruetten et al [23] reported in their article that satisfactory results were obtained in 90% of their patients, with a re-recurrence rate of 5.7% and no difference with open surgery.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Fusion surgery was required only in 1 patient. The dural injury risk in microendoscopic discectomy has been reported to be higher than in microsurgery [20,22]. Ruetten et al [23] reported in their article that satisfactory results were obtained in 90% of their patients, with a re-recurrence rate of 5.7% and no difference with open surgery.…”
Section: Discussionmentioning
confidence: 86%
“…The use of foraminoplasty in discs with marked migration increases the surgical success rate. However, it is reported that disc remnants can be seen in 5-13% of cases and post-operative temporary dysesthesia in up to 13% of cases, even in experienced hands [20,21]. Another disorder where PELD has become popular recently is recurrent disc herniation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations